A cognitive-pragmatic model for translation-shift analysis in descriptive case studies. Issue 1 (2nd January 2017) - Fotheringham, Christopher
Abstract: This paper proposes a taxonomy of shifts based on cognitive-pragmatic models of the translation process. The model for the analysis of shifts proposed here is designed to improve the quality of descriptive case studies in translation research. This model responds to the tendency of descriptive studies to analyse all translation shifts under the same rubric of neutrality. This paper establishes a clear distinction between strategies used in good faith by the translator to negotiate the cultural and contextual gaps between source-text and target-reader as opposed to mistranslations that result from misunderstanding of the source-text on the part of the translator. The theorising of these categories is based on a linking of cognitive models of the translation process with relevance theory. Several segments illustrative of the various types of shifts theorised are then chosen for comparative analysis. These are drawn from two works of contemporary South African fiction and their French translations. This paper does not claim to provide an exhaustive analysis of the shifts present in the chosen texts but rather to use these texts to illustrate the model presented.